Ate, Senador, Pilipino: A Critical Discourse Analysis of Kinship and Moral Authority in a Contemporary Philippine Political Speech - Leonardo Daquioag Tejano (Center for Southeast Asian Social Studies (CESASS), 2026)
This paper conducts a critical discourse analysis of Senator Imee Marcos's speech delivered on November 17, 2025, at an anti-corruption rally at a Christian religious organization, Luneta Park, Manila. The speech publicly accused her brother, President Ferdinand